Determination of the Structure and Catalytic Mechanism of Sorghum bicolor Caffeic Acid O-Methyltransferase and the Structural Impact of Three brown midrib12 Mutations. Issue 4 (19th June 2014) - Green, Abigail R.; Lewis, Kevin M.; Barr, John T.; Jones, Jeffrey P.; Lu, Fachuang; Ralph, John; Vermerris, Wilfred; Sattler, Scott E.; Kang, ChulHee
Abstract : The catalytic mechanism and substrate specificity of caffeic acid O-methyltransferase from Sorghum bicolor are deduced from crystal structures, site-directed mutagenesis, and kinetic and thermodynamic analyses. Abstract: Using S -adenosyl-methionine as the methyl donor, caffeic acid O -methyltransferase from sorghum ( Sorghum bicolor ; SbCOMT) methylates the 5-hydroxyl group of its preferred substrate, 5-hydroxyconiferaldehyde. In order to determine the mechanism of SbCOMT and understand the observed reduction in the lignin syringyl-to-guaiacyl ratio of three brown midrib12 mutants that carry COMT gene missense mutations, we determined the apo-form and S -adenosyl-methionine binary complex SbCOMT crystal structures and established the ternary complex structure with 5-hydroxyconiferaldehyde by molecular modeling. These structures revealed many features shared with monocot ryegrass ( Lolium perenne ) and dicot alfalfa ( Medicago sativa ) COMTs. SbCOMT steady-state kinetic and calorimetric data suggest a random bi-bi mechanism. Based on our structural, kinetic, and thermodynamic results, we propose that the observed reactivity hierarchy among 4, 5-dihydroxy-3-methoxycinnamyl (and 3, 4-dihydroxycinnamyl) aldehyde, alcohol, and acid substrates arises from the ability of the aldehyde to stabilize the anionic intermediate that results from deprotonation of the 5-hydroxyl group by histidine-267. Additionally, despite the presence of other phenylpropanoid substrates in vivo, sinapaldehyde is the preferential product, as demonstrated by its low K m for 5-hydroxyconiferaldehyde. Unlike its acid and alcohol substrates, the aldehydes exhibit product inhibition, and we propose that this is due to nonproductive binding of the S- cis-form of the aldehydes inhibiting productive binding of the S- trans-form. The S- cis-aldehydes most likely act only as inhibitors, because the high rotational energy barrier around the 2-propenyl bond prevents S- trans-conversion, unlike alcohol substrates, whose low 2-propenyl bond rotational energy barrier enables rapid S -cis/ S -trans-interconversion.